Tidal variation shaped microplastic enrichment patterns in mangrove blue carbon ecosystem of northern Beibu Gulf, China - Zhang, Li; Wang, Shujia; Jian, Qiying; Zhang, Peng; Lu, Yejin; Liu, Haoqi (Frontiers in Marine Science, 2022)
Mangroves are considered to be a sink for microplastics (MPs) due to their unique characteristics. Previous studies mainly focused on the spatial distribution of MPs, but few researchers have addressed the influence of tidal variation on this distribution, especially since the MP total number in mangroves was unknown. In this study, surface sediment samples were collected in mangroves from the Beibu Gulf, South China Sea, and the abundance, composition, and number of MPs were investigated. The results showed that MPs were widely present in all mangrove sediment samples, with abundances ranging from 26.67 ± 9.43 to 239.94 ± 37.80 items/kg. The distribution of MPs was heterogeneous among different sampling sites, with the highest levels in the Shankou (SK) area. The MP abundance in the same mangrove forest gradually increased from the low tidal zone to the high tidal zone, with the enrichment factor ranging from 1.50 to 4.00. The MP abundance was significantly correlated with particulate organic carbon (POC) (n = 12, R = 0.664, p < 0.05). Results showed that mangroves had an interception effect on MPs and factors affecting MP distribution in mangrove sediments included not only tides but also human activities, such as aquaculture, agriculture, and residential life. Finally, this paper estimated the MP total number in mangroves at different sampling areas and tidal zones, and the middle tidal zone was considered to be more accurate for MP pollution assessment in mangroves.